5-Aminolevulinic Acid Ameliorates Salinity-Mediated Growth, Pysiological and Biochemical Changes In Mustard (Brassica Juncea L.) (Bangladesh Journal of Agricultural Research, 2022)
5-aminolevulinic acid (ALA) is an important plant growth regulator which is derived from 5-carbon aliphatic amino acid. Here, ALA was examined in 12 dSm-1 salinity in growth and biochemical changes in mustard (Brassica juncea L. cv. BARI Sarisha-16) seedlings. Three NaCl mediated salinity levels (0, 8 and 12 dS m-1) were used with two ALA concentrations (30 and 60 mgL-1). Saline stress decreased plant height, root length, leaf area, dry mass accumulation, chlorophyll content, photosynthetic parameters, and K+, while proline (Pro), Na+, Na+/K+ ratio, antioxidant enzymatic activities, hydrogen peroxide (H2O2), superoxide (O2 •-), and melondialdehyde (MDA) content increased. Saline stressed mustard seedlings treated with 30 mgL-1 and 60 mgL-1 foliar application of ALA ameliorated the saline mediated inhibition in seedling growth i.e. increased plant height, root length, leaf area, and dry matter. ALA had also increase chlorophyll (Chl) content, net photosynthetic rate (Pn), stomatal conductance (Gs), intercellular CO2 concentration (Ci) and transpiration rate (Tr), proline content as well as the activities of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and ascorbate peroxidase (APX). In contrary, ALA decreased saline induced H2O2, O2 •-, and MDA while Na+ and Na+/K+ ratio increased. On the basis of the results, it was observed that ALA is a promising plant growth regulator which can improve plant survival under salinity.Bangladesh J. Agril. Res. 45(3): 217-231, September 2020